2021
DOI: 10.1186/s40575-021-00105-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of an angiotensin-converting enzyme gene variant in dogs

Abstract: Background Genetic heterogeneity of the canine angiotensin converting enzyme (ACE) gene is functionally important because the degree of aldosterone breakthrough with ACE-inhibitor therapy is greater in variant positive dogs compared to variant negative dogs, but the prevalence of the variant is not known. The purpose of this study was to determine ACE gene variant-positive prevalence in a population of 497 dogs of different breeds. Results Overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A previous study showed predispositions for the ACE variant in several breeds known to have genetically‐based heart disease (e.g., Irish Wolfhounds, Cavalier King Charles Spaniels), but there were insufficient numbers of DP in that study to assess breed predisposition 18 . Our study suggests a high prevalence of the ACE variant in DP.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…A previous study showed predispositions for the ACE variant in several breeds known to have genetically‐based heart disease (e.g., Irish Wolfhounds, Cavalier King Charles Spaniels), but there were insufficient numbers of DP in that study to assess breed predisposition 18 . Our study suggests a high prevalence of the ACE variant in DP.…”
Section: Discussionmentioning
confidence: 57%
“…The activities of ACE reported in our study are specific to the equilibrium dialysis approach and are not directly comparable to studies utilizing other methodologies. Another limitation of our study is the use of a single breed, which restricts applicability to other breeds, especially in light of breed predispositions for, and the potential influence of, the ACE variant 14,18 . Neutered male dogs also were not evaluated in our study because studies in people have indicated that estradiol is the major influencer of the RAAS and testosterone appears to have little effect on the cascade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, Chihuahua showed significantly higher UAldo:C compared to other breeds [ 9 ]. Polymorphism of angiotensin converting enzyme has been reported in dogs, with wide prevalence variability among breeds 36 . This gene variant has been associated with higher aldosterone levels and aldosterone breakthrough incidence in dogs [ 8 ].…”
Section: Discussionmentioning
confidence: 99%